EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGGKATAN KEPERCAYAAN DIRI MAHASISWA - Tri Velyna (Al-Rabwah, 2019)
Self-confidence can hamber social relations and academic achievement of students, a phenomenon that accurs in students at STAI Sangatta related to self-confidence that there are still many students who have not dared to ask and answer questions, have not dared to axplain in front of the class, cheat assignments and exam result friends, not confident with your own work. Untilization of group guidance services is an alternative that is applied increasing student confidence this study aims to leveal the affectiveness of group counseling services to increase student confidence. The research approach using quasi experiment with pre-test and post-test control group design is used to test whether group guidance services can increase student confidence. Two groups were selected using purposive sampling, namely at the reguler 3rd Islamic Education Management and weekend 3rd Islamic Education Management who came from outside the city of Sangatta. Each group consists of 10 college students. Group guidance services with application to the experimental group while the control group is not given group guidance services. Data aboult self-confidence was collected witha likert scale, then analyzed using the wilcoxon signed rank test and kolmogorov smirnov two independent samples with the help of SPSS version 20.00. The findings of this study are (1) there was a significant increase in students self-confidence scores after being given a group guidance service treatment, (2) there was no increase in students’ self-confidence scores that were not given a group guidance service treatment, (3) there were significant differences in the trust scores student self experimental group. Based on the research findings it can be concluded yhat student confidance can improved through group guindance services.